2015
DOI: 10.1016/j.forsciint.2015.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the initial composition of latent fingermark lipids by gas chromatography–mass spectrometry

Abstract: A more comprehensive understanding of the variability of latent fingermark composition is essential to improving current fingermark detection capabilities in an informed manner. Gas chromatography-mass spectrometry was used to examine the composition of the lipid fraction of latent fingermarks collected from a population of over 100 donors. Variations in the appearances of chromatograms from different donors were apparent in the relative peak sizes of compounds including free fatty acids, squalene, cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 51 publications
5
48
0
1
Order By: Relevance
“…T A B L E 1 Main constituents of human glands found in fingermark residues (Adapted from Champod, Lennard, Margot, & Stoilovic, 2016;Knowles, 1978;Ramotowski, 2001) A large number of papers have dealt with fingermark composition and their variability factors such as, the age or the gender of the donor, among other (Antoine, Mortazavi, Miller, & Miller, 2010;Asano, Bayne, Horsman, & Buchanan, 2002;Bohanan, 1998;Buchanan, Asano, & Bohanon, 1997;Cadd et al, 2015;Croxton, Baron, Butler, Kent, & Sears, 2006, 2010Frick, Chidlow, Lewis, & van Bronswijk, 2015;Fritz et al, 2013;Girod et al, 2012;Girod & Weyermann, 2014;Huynh, Brunelle, Halámková, Agudelo, & Halámek, 2015). New analytical techniques such as gas chromatography-mass spectrometry (GC-MS) (Croxton et al, 2006;Girod & Weyermann, 2014;Richmond-Aylor, Bell, Callery, & Morris, 2007;Weyermann, Roux, & Champod, 2011) or Fourier-transform infrared spectroscopy Johnston & Rogers, 2017a allow even more compounds to be detected and their interactions analyzed.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…T A B L E 1 Main constituents of human glands found in fingermark residues (Adapted from Champod, Lennard, Margot, & Stoilovic, 2016;Knowles, 1978;Ramotowski, 2001) A large number of papers have dealt with fingermark composition and their variability factors such as, the age or the gender of the donor, among other (Antoine, Mortazavi, Miller, & Miller, 2010;Asano, Bayne, Horsman, & Buchanan, 2002;Bohanan, 1998;Buchanan, Asano, & Bohanon, 1997;Cadd et al, 2015;Croxton, Baron, Butler, Kent, & Sears, 2006, 2010Frick, Chidlow, Lewis, & van Bronswijk, 2015;Fritz et al, 2013;Girod et al, 2012;Girod & Weyermann, 2014;Huynh, Brunelle, Halámková, Agudelo, & Halámek, 2015). New analytical techniques such as gas chromatography-mass spectrometry (GC-MS) (Croxton et al, 2006;Girod & Weyermann, 2014;Richmond-Aylor, Bell, Callery, & Morris, 2007;Weyermann, Roux, & Champod, 2011) or Fourier-transform infrared spectroscopy Johnston & Rogers, 2017a allow even more compounds to be detected and their interactions analyzed.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…C16:0 FAME is therefore the most abundant compound in natural fingerprint residues, which explains its very strong correlation. The FAMEs C14:0, C15:0, C18: also observed that hexadecenoic acid and squalene both contribute to variation in fingerprint residues [21,22,27]. As seen in Figure 7, face residues are more correlated with a branched C14:1 FAME and a branched 15:1 FAME (RT= 7.369 and 7.95, respectively).…”
Section: Intra-subject Variabilitymentioning
confidence: 79%
“…Inconsistencies like these have been attributed to contaminants such as cosmetic products, moisturizers, or even the genetic makeup of the individual [27].…”
Section: Sex Age and Race Determinationmentioning
confidence: 99%
See 2 more Smart Citations